The One-Stop Shop Approach: New Public Management Model in Transition Countries - Gashi, Kujtim; Krasniqi, Ibrahim (European Scientific Journal, ESJ, 2019)
Nowadays, One-stop shops (OSSs) are not rare, especially not in developed countries. In transition countries, they are currently very popular because the governments here are trying to address complaints about fragmentation in public service delivery. Specifically in those countries, the OSSs are faced very often with different problems beginning from the concept and design, followed by multiple implementation problems. This paper focuses on addressing the concept of development and new public management approach in transition countries using Kosovo as a case study. In addition, the paper seeks to determine drivers and barriers relevant to the strategic concept of adoption and implementation steps of OSSs in different public governance levels. OSS approaches are frequently established to bring win-win situations for citizens, clients, and service providers who are trying to find best solutions by delivering large number of services at lower cost. However, during the implementation phase, the political decision makers usually underestimate the complexities, costs, and risks of the OSS approach. This paper aims to establish general approach as a guide for the smooth implementation of OSS in order to avoid the unrealistic political and citizen expectations, conflicts, lack of resources, and dilemmas related to the OSS model that is most suitable for the certain region and governance level. During the research, the combined methodology was used by taking into consideration deductive approach and combining this with primary data collected through the interviews, face to face meetings, and, most importantly, comparing the different models from different countries in order to analyze and propose the most suitable model for Kosovo case of OSS. Whether or not the claimed benefits are achievable is an open question, and there are serious potential problems with the proposed system. Nevertheless, there is remarkably little evidence to support this claim.